KEPASTIAN HUKUM PENETAPAN LOKASI PENGADAAN TANAH BAGI PEMBANGUNAN BENDUNGAN BENER DI PURWOREJO - Tandiono, Sudargo; Lestari, Mega; Arwanto, Bambang (Lex Journal: Kajian Hukum & Keadilan, 2022)
Cases of corruption that occur in the natural resource sector can be realized because of some irregularities committed by officials who have authority in the natural resources sector itself related to the issuance of state administrative decisions, so that these actions do not harm the state in terms of finances but also have a negative impact on other humans and ecosystem integrity. The purpose of this research is to find out about the discrepancy between the Bener dam construction decisions and the findings found and how to prevent corruption in the natural resources sector in Indonesia. Keywords: Dam, Corruption, Decisions